Detecting myositis as a cause of unexplained dysphagia: Proposal for a diagnostic algorithm. (16th December 2021) - Labeit, Bendix; Grond, Thalia; Beule, Achim G.; Boehmer, Maik; Thomas, Christian; Muhle, Paul; Claus, Inga; Roderigo, Malte; Rudack, Claudia; Wiendl, Heinz; Dziewas, Rainer; Warnecke, Tobias; et al.
Abstract: Background and purpose: Idiopathic inflammatory myopathy (IIM) can present with dysphagia as a leading or only symptom. In such cases, diagnostic evaluation may be difficult, especially if serological and electromyographical findings are unsuspicious. In this observational study we propose and evaluate a diagnostic algorithm to identify IIM as a cause of unexplained dysphagia. Methods: Over a period of 4 years, patients with unexplained dysphagia were offered diagnostic evaluation according to a specific algorithm: The pattern of dysphagia was characterized by instrumental assessment (swallowing endoscopy, videofluoroscopy, high‐resolution manometry). Patients with an IIM‐compatible dysphagia pattern were subjected to further IIM‐focused diagnostic procedures, including whole‐body muscle magnetic resonance imaging, electromyography, creatine kinase blood level, IIM antibody panel and, as a final diagnostic step, muscle biopsy. Muscle biopsies were taken from affected muscles. In cases where no other muscles showed abnormalities, the cricopharyngeal muscle was targeted. Results: Seventy‐two patients presented with IIM‐compatible dysphagia as a leading or only symptom. As a result of the specific diagnostic approach, 19 of these patients were diagnosed with IIM according to the European League Against Rheumatism (EULAR) criteria. Eighteen patients received immunomodulatory therapy as a result of the diagnosis. Of 10 patients with follow‐up swallowing examination, dysphagia improved in three patients after therapy, while it remained at least stable in six patients. Conclusions: Idiopathic inflammatory myopathy constitutes a potentially treatable etiology in patients with unexplained dysphagia. The diagnostic algorithm presented in this study helps to identify patients with an IIM‐compatible dysphagia pattern and to assign those patients for further IIM‐focused diagnostic and therapeutic procedures. Abstract : The diagnostic algorithm presented in this study helps to identify patients with a myositis‐compatible dysphagia pattern and to assign those patients for further myositis‐focused diagnostic and therapeutic procedures.